A Prevalence Study of Psychosocial Distress in Adolescents and Young Adults With Cancer. Issue 3 (May 2017) - Xie, Jianfei; Ding, Siqing; He, Siqi; Duan, Yinglong; Yi, Kaigui; Zhou, Jianda
Abstract : Background: Psychosocial distress is common among cancer patients. Significant associations between coping and social support with distress and quality of life in adult cancer patients have been identified before, but little is known about the interrelationships between distress, medical coping, and social support in adolescents and young adults (AYAs). Objective: The aims of this study are to investigate the prevalence of psychological distress in Chinese AYAs with cancer and examine the associations among distress, anxiety and depression, medical coping, and social support in the same population. Methods: A total of 610 AYA patients were recruited for this study; 551 patients completed the Chinese version of the National Comprehensive Cancer Network Distress Thermometer (DT), the Hospital Anxiety and Depression Scale, the Medical Coping Modes Questionnaire, and the Social Support Rating Scale. Results: The prevalence of psychological distress was 89.1% in Chinese AYAs with cancer. The DT scores were the highest in the 21- to 25-year-old patients; the DT scores were positively correlated with anxiety and depression ( P < .01) but negatively correlated with medical coping and social support ( P < .01). Conclusion: The prevalence of psychological distress in AYA cancer patients was higher than that in the general cancer population. Medical coping and social support can lower the prevalence of psychological distress in AYA cancer patients. Implications for Practice: Findings suggest the need for evidence-based intervention strategies to enhance medical coping and social support in AYA cancer patients. Nurses are crucial to implementing psychological interventions in AYA cancer patients.